German division as shared experience interdisciplinary perspectives on the postwar everyday - Carter, Erica 1957-; Palmowski, Jan 1965-; Schreiter, Katrin (Berghahn, 2019)
"Despite the nearly three decades since German reunification, there remains little understanding of the ways in which experiences overlapped across East-West divides. German Division as Shared Experience considers everyday life across the two Germanies, using perspectives from history, literary and cultural studies, anthropology and art history to explore how interconnections as well as fractures between East and West Germany after 1945 were experienced, lived and felt. Through its novel approach to historical method, the volume points to new understandings of the place of narrative, form and lived sensibility in shaping Germans' simultaneously shared and separate experiences of belonging during forty years of division from 1945 to 1990"--
Keywords: Geschichte 1945-1990; Alltag; Teilung; Deutschland; Germany (East) / Social life and customs; Germany (West) / Social life and customs; Germany (East) / Intellectual life; Germany (West) / Intellectual life; Intercultural communication / Germany (East) / History; Intercultural communication / Germany (West) / History; Germany (East) / Relations / Germany (West); Germany (West) / Relations / Germany (East); Germany / History / 1945-1990; Intellectual life; Intercultural communication; International relations; Manners and customs; Germany; Germany (East); Germany (West); 1945-1990; History; Aufsatzsammlung